1996
DOI: 10.1093/clinids/22.6.1092
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Outbreak of Burkholderia pickettii Infection Due to a Manufactured Intravenous Product Used in Three Hospitals

Abstract: Forty-six cases of nosocomial infection caused by Burkholderia pickettii were reported between June and November 1993 in three metropolitan hospitals in Madrid. A case-control study of the outbreak was conducted to identify its cause. Seventy-four percent of the patients were males; the mean age +/- SD of the patients was 54 +/- 20 years. Sixty-five percent of the patients presented with some gastrointestinal disorder, and 80% had a peripheral catheter; 98% were treated with intravenous fluids, and 96% were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…28 These can be given intravenously, 8 given as a drip solution, 25 used to clean wounds, or used for endotracheal suctioning. 27 These have led to both bloodstream (bacteraemia) and respiratory infections.…”
Section: Instances Of Infectionmentioning
confidence: 99%
“…28 These can be given intravenously, 8 given as a drip solution, 25 used to clean wounds, or used for endotracheal suctioning. 27 These have led to both bloodstream (bacteraemia) and respiratory infections.…”
Section: Instances Of Infectionmentioning
confidence: 99%
“…9 Therefore, many of the cases of infection with R. pickettii were due to contaminated water or aqueous solutions given intravenously. 5,6,10,11 Interestingly, even ''sterile'' medical products like ranitidine 12 and saline solution 13,14 were reported to be contaminated with R. pickettii. Several infections of patients with permanent indwelling intravenous devices like central venous catheters or Port-A-Caths have been described.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Cases in which B. pickettii infection has been reported, generally involve simple bacteremia related to contamination of hospital pharmacy sources. [4][5][6] Many cases were associated with a direct inoculation of the blood or another site of infection. Maki et al 4 reported an outbreak of nosocomial bacteremias caused by B. pickettii in surgical patients and the linked this to the first traces in a contaminated narcotic.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The cases in which infection has been reported generally involve simple bacteremia, related to contamination of manufactured products. [4][5][6] The authors describe a rare case of B. pickettii spondylitis in a healthy adult.…”
Section: Introductionmentioning
confidence: 99%